The unicompartmental knee is the preferred side in individuals with both a unicompartmental and total knee arthroplasty - Wiik, Anatole Vilhelm (Knee Surg Sports Traumatol Arthrosc, 2019)
PURPOSE: To determine the preferred knee in patients with both one total and one unicompartmental knee arthroplasty. METHOD: Patients simply with a unicompartmental (UKA) and total knee arthroplasty (TKA) on contralateral sides were retrospectively screened from three senior knee surgeon’s logs over a 15 year period. Patients safe and free from other diseases to affect gait were approached. A total of 16 patients (mean age 70 ± 8) agreed to ground reaction force testing on an instrumented treadmill at a fair pace and incline. A gender-ratio identical group of 16 healthy control subjects (mean age 67 ± 10) and 16 patients with ipsilateral medial knee OA (mean age 66 ± 7) were analysed to compare. RESULTS: Radiographically the mode preoperative Kellgren–Lawrence knee grade for each side was 3. Postoperatively, the TKA side had a mean coronal femoral component alignment of 7° and a mean tibial coronal alignment of 89° with a mean posterior slope of 5° in the sagittal plane. The UKA side had a mean coronal femoral component alignment of 7° and a mean tibial coronal alignment of 86° with a mean posterior slope of 4° in the sagittal plane. In 7 patients, the TKA was the first procedure, while 6 for the UKA and 3 done simultaneously. Gait analysis demonstrated in both walking conditions the UKA limb was the preferred side through all phases of loading (p < 0.05) and nearer to normal than the TKA limb when compared to healthy controls and patients with knee OA. The greatest difference was observed between the transition of weight acceptance and midstance (p = 0.008), when 22% more load was taken by the UKA side. CONCLUSION: By using a dynamic metric of an everyday activity, a distinct gait difference between differing arthroplasty types were established. A more natural loading pattern can be achieved with unicompartmentals as compared to total knees. LEVEL OF EVIDENCE: Retrospective comparative study, Level III.